Pemanfaatan Sekam Padi untuk Pembuatan Briket Arang Sebagai Energi Alternatif - Alala, Pratama Sandi; HM, Gatot Basuki; Erdhianto, Yoniv; Munir, Misbahul (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2023)
ABSTRACT The increasing need for fuel consumption is not in line with the diminishing availability of fossil fuels. At every rice mill, there will always be a pile, even mountains of husks, which are getting higher and higher. This study was conducted to determine the effectiveness of the management of rice husk waste into briquettes, which can be a solution that can convert agricultural waste into fuel with a fairly good conversion efficiency. The method used in this research is the carbonization method. The carbonization or charcoal process is the process of converting raw materials into black carbon by burning in a closed space with limited or minimal air. In the testing process, the researcher used 2 factors to determine the results of the two samples, namely the physical factor, namely the factor used to test the physical sample and the combustion effectiveness factor, namely the factor used to determine how long it took to burn the sample.